UV-C assisted microwave drying of Ashwagandha (Withania somnifera) leaves: Drying kinetics, fuzzy logic-based model evaluation, and selected optical and phytochemical attributes - Sudarshan Ramanathan; S. Samuel Nirmalsingh; P. Dinesh Kumar; Sumit Sudhir Pathak (Innovative Food Science & Emerging Technologies, 2026)

Understanding the interactions between soil moisture and other hydro-meteorological parameters during heatwaves over upper Assam in North-East India - Aniket Chakraborty; Binita Pathak; Partha Pratim Gogoi; U. P. V. Sreelakshmi; Partha Jyoti Sahu; Pradip Kumar Bhuyan (Meteorology and Atmospheric Physics, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Influence of Soil Carbon Pools and Indices on Zinc Sorption Mechanisms and Distribution in Diverse Potato-based Cropping Systems of the Western Indo-Gangetic Plains - Shivam Singh; Debashis Dutta; Satendra Kumar; Jagannath Pathak; Uday Pratap Shahi; B. P. Dhyani; Ankit Tiwari; Mahendra Pratap Singh; R. B. Verma; Richa Raghuvanshi (Potato Research, 2026)

Managing plant health in changing climate: Indian context - Himanshu Pathak; Prashant P. Jambhulkar; Dilip Ghosh (Indian Phytopathology, 2026)

Arsenate adsorption onto hydrous ferric oxide: Insights from triple layer surface complexation modeling - Hafsa Nazir; Raheena Moozhikkal; Bhawna Thakur; Shray Pathak; Pushpendra P. Singh (Journal of Geochemical Exploration, 2026)

Elucidating the Conjoint Effect of Nano, Conventional and Bio-Fertilizer on Steering Sugarcane Productivity, Quality and Soil Health - Mona Nagargade; Vishal Tyagi; Dileep Kumar; Sudhir Kumar Shukla; Preeti Singh; Rajeev Kumar; Ashwini Dutt Pathak; V. P. Jaiswal; M. K. Tripathi; A. P. Dwivedi; Lalan Sharma; Sanjay Singh Rathore; et al. (International Journal of Plant Production, 2026)

Targeting west nile virus replication by xanthine inhibitors - Theresa H. Nguyen; Jessica L. Smith; Shuklendu D. Karyakarte; John P. Tillotson; Sarath C. Sarngadharan; Fuad Al Abir; Jake Y. Chen; Sixue Zhang; Lynn Rasmussen; Robert Bostwick; Alec J. Hirsch; Corinne E. Augelli-Szafran; et al. (Medicinal Chemistry Research, 2025)

Scytonemin Production by Cyanobacteria: A Threat To Algal Stromatolites in Salkhan Fossil Park, India - Jainendra Pathak; Rajneesh; Vidya Singh; Neha Kumari; Rajeshwar P. Sinha (Geoheritage, 2025)

Climate Resilient Crop Varieties: Mainstreaming to Improve Yield and Moderate Farmers’ Risk - D. K. Yadava; Ranjay K. Singh; V. B. Patel; T. R. Sharma; S. K. Singh; Sudhakar Pandey; P. R. Choudhury; Firoz Hossain; R. R. Burman; U. S. Gautam; Himanshu Pathak (Anthropocene Science, 2025)

Hydrogen, single-carbon compounds, and thermal regime in the oceanic ultramafic-dominated lithosphere: insights from a deep borehole on the Atlantis Massif - Susan Q. Lang; C. Geoffrey Wheat; Kristin L. Dickerson; Mark K. Reagan; Ivan P. Savov; Jordyn A. Robare; William J. Brazelton; Johanna Suhonen; Oscar Cavazos; Andrew McCaig; Peter Blum; Natsue Abe; et al. (Geochimica et Cosmochimica Acta, 2025)

Recent advancement on nanotechnology and natural compounds for skin UV protection: a review - M. J. Saadh; V. Jain; M. M. Rekha; P. K. Pathak; H. M. Ahmed; K. Satyam Naidu; B. Juneja; F. Faez Sead; M. Dehghanipour (International Journal of Environmental Science and Technology, 2025)

Design and Validation of a Low-Cost, Portable Arduino-Based Platform for Assessing Physicochemical Drinking Water Quality Across Urban and Peri-urban Areas of Delhi and Surrounding Regions - Arjun Singh; Rahul Arya; Nikki Choudhary; Navraj Poudel; Poonam Arora; K. K. Maurya; T. K. Mandal; S. K. Sharma; Prashant Kumar; Saurabh Pathak; R. P. Pant (Water Conservation Science and Engineering, 2025)

Appraisal on Energy Coefficients in Energetic Analysis of Agricultural Production System and Energetic Assessment on Sugarcane production - P. Subramanian; R. Mahendiran; B. Prabha; Gitanjali Jothiprakash; Ramesh Desikan; Bhargav Vinod Kumar; K. C. Pandey; Bhim Sen Pathak (Sugar Tech, 2025)

Integration of Bioproducts with NPK for Improving Physiological Efficiency of Sugarcane and Sustaining Soil Quality Parameters in Subtropical India - V. P. Jaiswal; S. K. Shukla; Lalan Sharma; A. D. Pathak; Asha Gaur; Abhay Srivastava; Rishi Kumar; Mamta Chaoudhary (Sugar Tech, 2025)

Combined Genome-Wide Association Study and Expression Analysis Unravels Candidate Genes Associated with Seed Weight in Moth Bean [Vigna aconitifolia (Jacq.) Marechal] - Arvind Kumar Yadav; Chandan Kumar Singh; Dhammaprakash P. Wankhede; Rajwant K. Kalia; Seema Pradhan; Shraddha Ujjainwal; Tanmaya Kumar Sahu; N. S. Nathawat; R. K. Kakani; Reena Rani; Rajesh Kumar; Rakesh Pathak; et al. (Journal of Plant Growth Regulation, 2025)

Integration of Mycorrhizae, Azotobacter and Pseudomonas spp (PSB) with NPK and their Effects on Sugarcane Crop and Soil Health in Uttar Pradesh, India - M. K. Tripathi; S. K. Shukla; V. P. Jaiswal; Lalan Sharma; Mona Nagargade; A. D. Pathak; A. P. Dwivedi; Ankur Tripathi; V. K. Singh; V. P. Singh; Ajay Ranka (Sugar Tech, 2025)

Size dependent noble metal nanoparticles modified DNA: MD-simulation studies - Sourav Mazumdar; Ankush Chauhan; Niranjan Kumar Mridha; Narendra Nath Ghosh; Suman Adhikari; Surajit Pathak; Asoke P. Chattopadhyay; Nabajyoti Baildya (Next Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Flow-by-Flow Paleofield and Virtual Dipole Moment Analysis in the Mandla Lobe, Eastern Deccan Volcanic Province - Bhuvan K. Tamta; Vamdev Pathak; J. P. Shrivastava; Arun Kumar Gupta; Girish Ch. Kothyari (Pure and Applied Geophysics, 2025)

Zinc Adsorption–Desorption Behavior and Sequential Extractable Pools in Sugarcane-Based Cropping Systems of Western Indo-Gangetic Plain - Shivam Singh; Satendra Kumar; Debashis Dutta; Richa Raghuvanshi; Jagannath Pathak; Uday Pratap Shahi; B. P. Dhyani; Ankit Kumar; Mahendra Pratap Singh; Himanshu Panday; A. K. Shah (Sugar Tech, 2024)

Efficiency and economic assessment of wind turbine-powered pumped hydro-compressed air storage coupled with alkaline fuel cell using hybrid approach - K. E. Lakshmiprabha; U. Arun Kumar; Pankaj Pathak; P. Elangovan (Clean Technologies and Environmental Policy, 2024)

Development of a High-Fidelity Benchtop Model for Simultaneous Flow, Pressure, and Imaging Assessment of Transarterial Embolization Procedures - Prateek C. Gowda; Robert M. Weinstein; Akanksha Bhargava; Janaka Senarathna; Ryan Q. Stewart; Pallavi V. Ekbote; Mantej Singh; Emily Guan; Serena Banghar; Arvind P. Pathak; Clifford R. Weiss (Cardiovascular Engineering and Technology, 2024)

Crustal origin for olivine in the lunar Shioli crater ejecta boulders: Insights from the geological setting of Theophilus crater and Nectaris basin - P. Senthil Kumar; Abhisek Mishra; Vivek Krishnan; Netra S. Pillai; Sumit Pathak; Sriram S. Bhiravarasu; Shyama Narendranath; K. Jaya Prasanna Lakshmi; Satadru Bhattacharya (Icarus, 2024)

Development of antibody to virulence factor flagellin and its evaluation in screening Ralstonia pseudosolanacearum - Shalini Bhatt; S. Merwyn P. Raj; Neha Faridi; Dinesh Pathak; Ankur Agarwal; Shraddha P. Mishra (Brazilian Journal of Microbiology, 2024)

Multimodality imaging reveals angiogenic evolution in vivo during calvarial bone defect healing - Yunke Ren; Xinying Chu; Janaka Senarathna; Akanksha Bhargava; Warren L. Grayson; Arvind P. Pathak (Angiogenesis, 2024)

Climate change impacts on insect pests for high value specialty crops in California - Prakash Kumar Jha; Ning Zhang; Jhalendra P. Rijal; Lauren E. Parker; Steven Ostoja; Tapan B. Pathak (Science of The Total Environment, 2024)

Dual metal ion (Fe3+ and As3+) sensing and cell bioimaging using fluorescent carbon quantum dots synthesised from Cynodon dactylon - Sweta Gurung; Neha; Nimmala Arun; Mayank Joshi; Tanya Jaiswal; Anand P. Pathak; Parimal Das; Amaresh Kumar Singh; Ajay Tripathi; Archana Tiwari (Chemosphere, 2023)

Quantification of Cerebral Vascular Autoregulation Immediately Following Resuscitation from Cardiac Arrest - Yucheng Shen; Qihong Wang; Hiren R. Modi; Arvind P. Pathak; Romergryko G. Geocadin; Nitish V. Thakor; Janaka Senarathna (Annals of Biomedical Engineering, 2023)

Phylogenetic distribution, structural analysis and interaction of nucleotide excision repair proteins in cyanobacteria - Prashant R. Singh; Amit Gupta; Rajneesh; Jainendra Pathak; Rajeshwar P. Sinha (DNA Repair, 2023)

Observations on the decadal variability of aerosol in eastern Himalayan foothills: Evidence of an anthropologically induced positive shift - Tamanna Subba; Binita Pathak; Mukunda M. Gogoi; P. Ajay; Papori Dahutia; Aniket Chakraborty; Pradip K. Bhuyan (Atmospheric Environment, 2023)

Thyroid hormone dynamics of Tharparkar and Sahiwal cattle during induced heat stress - Anjali; Gururaj VK; Lipika Sarma; M. Tripathi; Med Ram Verma; Vinay Verma; M. C. Pathak; H. A. Samad; V. P. Maurya; V. S. Chouhan; Gyanendra Singh (Tropical Animal Health and Production, 2023)

Crop Residue Recycling Affecting Carbon Sequestration, Nutrients Availability and Crop Yields in Rice–Wheat and Sugarcane–Ratoon–Wheat System - V. P. Jaiswal; S. K. Shukla; Lalan Sharma; A. D. Pathak (Sugar Tech, 2023)

Adsorption of congo red using carbon from leaves and stem of water hyacinth: equilibrium, kinetics, thermodynamic studies - A. Extross; A. Waknis; C. Tagad; V. V. Gedam; P. D. Pathak (International Journal of Environmental Science and Technology, 2023)

Purification, characterization and assessment of stability, reactive oxygen species scavenging and antioxidative potentials of mycosporine-like amino acids (MAAs) isolated from cyanobacteria - Deepak K. Singh; Jainendra Pathak; Abha Pandey; Rajneesh; Vidya Singh; Rajeshwar P. Sinha (Journal of Applied Phycology, 2022)

Plant Quarantine Regulations With Reference to Sugarcane in India: Strengths and Challenges - S. N. Sushil; Deeksha Joshi; Sharmila Roy; G. P. Rao; A. D. Pathak (Sugar Tech, 2022)

Diversification Options in Sugarcane-Based Cropping Systems for Doubling Farmers’ Income in Subtropical India - S. K. Shukla; Lalan Sharma; V. P. Jaiswal; A. P. Dwivedi; S. K. Yadav; A. D. Pathak (Sugar Tech, 2022)

Prolonged effects of DPP-4 inhibitors on steato-hepatitic changes in Sprague–Dawley rats fed a high-cholesterol diet - Rashmi Pathak; Avinash Kumar; Henry A. Palfrey; Kirsten P. Stone; Narayan R. Raju; Thomas W. Gettys; Subramanyam N. Murthy (Inflammation Research, 2022)

Molecular mapping of CLCuD resistance introgressed from synthetic cotton polyploid in upland cotton - Suruchi Vij; Dharminder Pathak; Pankaj Rathore; Harish Kumar; P. S. Sekhon; Dharminder Bhatia; Parveen Chhuneja; Kuldeep Singh (Journal of Genetics, 2022)

Long-Term Yield of Rice–Rice System with Different Nutrient Management in Eastern India: Effect of Air Temperature Variability in Dry Season - Manish Debnath; Rahul Tripathi; Sumanta Chatterjee; Md. Shahid; B. Lal; Priyanka Gautam; N. N. Jambhulkar; S. Mohanty; D. Chatterjee; B. B. Panda; P. K. Nayak; P. Bhattacharyya; et al. (Agricultural Research, 2022)

Functional Convergence of Motor and Social Processes in Lobule IV/V of the Mouse Cerebellum - Owen Y. Chao; Hao Zhang; Salil Saurav Pathak; Joseph P. Huston; Yi-Mei Yang (The Cerebellum, 2021)

Vertical root distribution in Himalayan trees: about half of roots occur below 30 cm, the generally sampled depth - Girish C. Pathak; Harshita Joshi; Ripu Daman Singh; Ashish Tewari; Rajiv Pandey; Surendra P. Singh (Tropical Ecology, 2021)

Variation in the Nutritional Composition of Soft and Hard Blue Swimming Crabs ( Portunus pelagicus ) Having Good Export Potential - Neeraj Pathak; Robinson Jeya Shakila; Geevaretnam Jeyasekaran; Padmavathy P; Neethiselvan N; R. Shalini; Ulaganathan Arisekar; Akalesh Patel; Udhaya Kumar; Asha Hema Malini; R Mayilvahnan (Journal of Aquatic Food Product Technology, 2021)

Impact of the Federal Conservation Program Participation on Conservation Practice Adoption Intensity in Louisiana, USA - Santosh Pathak; Krishna P. Paudel; Naveen C. Adusumilli (Environmental Management, 2021)

Identification of Appropriate Agri-technologies Minimizing Yield Gaps in Different Sugarcane-Growing States of India - S. K. Shukla; Lalan Sharma; V. P. Jaiswal; A. D. Pathak; S. K. Awasthi; Adil Zubair; S. K. Yadav (Sugar Tech, 2021)

Effect of Long-Term Organic Fertilization in Flooded Rice Soil on Phosphorus Transformation and Phosphate Solubilizing Microorganisms - Dibyendu Chatterjee; A. K. Nayak; Annapurna Mishra; C. K. Swain; U. Kumar; D. Bhaduri; P. Panneerselvam; B. Lal; P. Gautam; H. Pathak (Journal of Soil Science and Plant Nutrition, 2021)

Potassium Influencing Physiological Parameters, Photosynthesis and Sugarcane Yield in Subtropical India - V. P. Jaiswal; S. K. Shukla; Lalan Sharma; Ishwar Singh; A. D. Pathak; Mona Nagargade; Arup Ghosh; C. Gupta; Asha Gaur; S. K. Awasthi; Raghvendra Tiwari; Abhay Srivastava; et al. (Sugar Tech, 2021)

Selection and validation of differentially expressed metabolic and immune genes in weaned Ghurrah versus crossbred piglets - A. Karthikeyan; Shalu Kumari Pathak; Amit Kumar; B. A. A Sai Kumar; Aamir Bashir; Akansha Singh; N. R. Sahoo; B. P. Mishra (Tropical Animal Health and Production, 2021)

Sugarcane Yield Using Minimum Tillage Technology Through Subsoiling: Beneficial Impact on Soil Compaction, Carbon Conservation and Activity of Soil Enzymes - S. K. Shukla; V. P. Jaiswal; Lalan Sharma; A. D. Pathak; Akhilesh Kumar Singh; Rajendra Gupta; S. K. Awasthi; Asha Gaur; Adil Zubair; Raghvendra Tiwari (Sugar Tech, 2020)

Retraction Note: Engineered Polyallylamine Nanoparticles for Efficient In Vitro Transfection - Atul Pathak; Anita Aggarwal; Raj K. Kurupati; Soma Patnaik; Archana Swami; Yogendra Singh; Pradeep Kumar; Suresh P. Vyas; Kailash C. Gupta (Pharmaceutical Research, 2020)

Flood vulnerability and its influencing factors - Santosh Pathak; Hari Krishna Panta; Thaneshwar Bhandari; Krishna P. Paudel (Natural Hazards, 2020)

Characterization of bioaerosols in Northeast India in terms of culturable biological entities along with inhalable, thoracic and alveolar particles - Binita Pathak; Debajit Borah; Ankita Khataniar; P K Bhuyan; A K Buragohain (Journal of Earth System Science, 2020)

Fish community and habitat diversity profiling of Luni, an ephemeral saline river from Thar Desert of India for conservation and management - Ajey Kumar Pathak; G. Kantharajan; V. P. Saini; Ravi Kumar; Rajesh Dayal; Vindhya Mohindra; Kuldeep K. Lal (Community Ecology, 2020)

Cyanobacterial Secondary Metabolite Scytonemin: A Potential Photoprotective and Pharmaceutical Compound - Jainendra Pathak; Abha Pandey; Pankaj K. Maurya; Rajneesh Rajneesh; Rajeshwar P. Sinha; Shailendra P. Singh (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Physiological and Biochemical Response of a Hot-Spring Cyanobacterium Nostoc Sp. Strain HKAR-2 to Aluminum Toxicity - Vinod K. Kannaujiya; Deepak Kumar; Jainendra Pathak; Rajneesh; Rajeshwar P. Sinha (Water, Air, & Soil Pollution, 2020)

Photoprotective role of UV-screening pigment scytonemin against UV-B-induced damages in the heterocyst-forming cyanobacterium Nostoc sp. strain HKAR-2 - Abha Pandey; Jainendra Pathak; Deepak K. Singh; Haseen Ahmed; Vidya Singh; Deepak Kumar; Rajeshwar P. Sinha (Brazilian Journal of Botany, 2020)

Impact of microphysics parameterizations and horizontal resolutions on simulation of “MORA” tropical cyclone over Bay of Bengal using Numerical Weather Prediction Model - Lakhima Chutia; Binita Pathak; Ajay Parottil; P. K. Bhuyan (Meteorology and Atmospheric Physics, 2019)

Immunohistochemical localization of estrogen receptor alpha (ERα) in the oviduct of Indian buffalo during follicular and luteal phases of estrous cycle - Devendra Pathak; Neelam Bansal; Opinder Singh; Kuldip Gupta; S. P. S. Ghuman (Tropical Animal Health and Production, 2019)

The incretin enhancer, sitagliptin, exacerbates expression of hepatic inflammatory markers in rats fed a high-cholesterol diet - Rashmi Pathak; Avinash Kumar; Henry A. Palfrey; Laura A. Forney; Kirsten P. Stone; Narayan R. Raju; Thomas W. Gettys; Subramanyam N. Murthy (Inflammation Research, 2019)

Obtaining best parameterization scheme of RegCM 4.4 for aerosols and chemistry simulations over the CORDEX South Asia - P. Ajay; B. Pathak; F. Solmon; P. K. Bhuyan; F. Giorgi (Climate Dynamics, 2019)

In vivo high-resolution diffusion tensor imaging of the developing neonatal rat cortex and its relationship to glial and dendritic maturation - Markus Breu; Dominik Reisinger; Liangcheng Tao; Dan Wu; Yajing Zhang; Matthew D. Budde; Ali Fatemi; Arvind P. Pathak; Jiangyang Zhang (Brain Structure and Function, 2019)

Kinetics of Total Volatile Basic Nitrogen and Trimethylamine Formation in Stored Rohu ( Labeo rohita ) Fish - Pramod K. Prabhakar; Prem P. Srivastav; Sant S. Pathak (Journal of Aquatic Food Product Technology, 2019)

Green Technologies for Improving Cane Sugar Productivity and Sustaining Soil Fertility in Sugarcane-Based Cropping System - S. K. Shukla; S. Solomon; Lalan Sharma; V. P. Jaiswal; A. D. Pathak; Priyanka Singh (Sugar Tech, 2019)

Wheat TaVIT2D restores phenotype and mediates iron homeostasis during growth of Arabidopsis thaliana in iron-deficient conditions - Raja Jeet; Sudhir P. Singh; Siddharth Tiwari; Promila Pathak (Plant Physiology Reports, 2019)

RuBisCo activase—a catalytic chaperone involved in modulating the RuBisCo activity and heat stress-tolerance in wheat - Ranjeet Ranjan Kumar; Suneha Goswami; Kavita Dubey; Khushboo Singh; Jyoti P. Singh; Ashok Kumar; Gyanendra Kumar Rai; Shiv Dhar Singh; Suman Bakshi; Bhupinder Singh; Himanshu Pathak; Viswanathan Chinnusamy; et al. (Journal of Plant Biochemistry and Biotechnology, 2019)

Ecosystem services in different agro-climatic zones in eastern India: impact of land use and land cover change - Rahul Tripathi; K. C. Moharana; A. D. Nayak; B. Dhal; Md Shahid; B. Mondal; S. D. Mohapatra; P. Bhattacharyya; Nuala Fitton; Pete Smith; A. K. Shukla; H. Pathak; et al. (Environmental Monitoring and Assessment, 2019)

Impact of seasonal thermal stress on physiological and blood biochemical parameters in pigs under different dietary energy levels - P. K. Pathak; R. Roychoudhury; J. Saharia; M. C. Borah; D. J. Dutta; R. Bhuyan; D. Kalita (Tropical Animal Health and Production, 2018)

Composition and functional property of photosynthetic pigments under circadian rhythm in the cyanobacterium Spirulina platensis - Deepak Kumar; Vinod K. Kannaujiya; Richa; Jainendra Pathak; Shanthy Sundaram; Rajeshwar P. Sinha (Protoplasma, 2018)

Climatic variability of the Pacific and Atlantic Oceans and western US snowpack - Pratik Pathak; Ajay Kalra; Kenneth W. Lamb; William P. Miller; Sajjad Ahmad; Rajesh Amerineni; Devi P. Ponugoti (International Journal of Climatology, 2018)
This study examines the changing characteristics of snow water equivalent (SWE) in western United States and their teleconnections with large‐scale variability of the Pacific and Atlantic Oceans. This study evaluated the relationship among sea surface temperatures (SST), 500‐mbar geopotential height (Z 500 ), 500‐mbar east–west wind (U 500 ), and western United States SWE (1 March, 1 April, and 1 May). The averages of SST, Z 500 , and U 500 were computed to create a lead time of 2–10 months. Three different 6‐month series were computed – January–June, April–September, and July–December – and were correlated with SWE stations in the western United States. The study utilized singular‐value decomposition (SVD) for a period of 1961–2016 to correlate the SWE and climate indices. SVD was applied between the standardized SST and SWE to obtain their correlation and to evaluate connection with Z 500 and U 500 within the same SVD relationship. Specifically, SVD was not applied independently on each variable prior to this study. The correlations were observed to increase as the lead time decreased. First mode SVD showed a pronounced non‐El Niño‐Southern Oscillation short‐wave train for the July–December climate in the Z 500 data; this terminated over the Great Lakes region, and was strongly correlated with the warming of the SST near the east coast of Japan, resulting in decreased SWE in the study area. Second mode SVD showed a negative correlation between SWE stations in Colorado and Utah and SST near the Asian and Australian continents. The associations between climate indices and SWE that were identified during this study could be used to improve long‐term forecasts, resulting in better management of water resources in the region.

miR-217–casein kinase-2 cross talk regulates ERK activation in ganglioglioma - Atreye Majumdar; Fahim Ahmad; Touseef Sheikh; Reshma Bhagat; Pankaj Pathak; Shanker Datt Joshi; Pankaj Seth; Vivek Tandon; Manjari Tripathi; P. Saratchandra; Chitra Sarkar; Ellora Sen (Journal of Molecular Medicine, 2017)

RNA Seq analysis for transcriptome profiling in response to classical swine fever vaccination in indigenous and crossbred pigs - Shalu Kumari Pathak; Amit Kumar; G. Bhuwana; Vaishali Sah; Vikramadiya Upmanyu; A. K. Tiwari; A. P. Sahoo; A. R. Sahoo; Sajjad A. Wani; Manjit Panigrahi; N. R. Sahoo; Ravi Kumar (Functional & Integrative Genomics, 2017)

Soil Carbon Sequestration and Crop Yields in Rice–Wheat and Sugarcane–Ratoon–Wheat Cropping Systems Through Crop Residue Management and Inoculation of Trichoderma viride in Subtropical India - S. K. Shukla; Swaha Shee; S. K. Maity; S. Solomon; S. K. Awasthi; Asha Gaur; A. D. Pathak; V. P. Jaiswal (Sugar Tech, 2017)

Simulation of leaf blast infection in tropical rice agro-ecology under climate change scenario - K. Viswanath; P. Sinha; S. Naresh Kumar; Taru Sharma; Shalini Saxena; Shweta Panjwani; H. Pathak; Shalu Mishra Shukla (Climatic Change, 2017)

Control of campylobacter in poultry industry from farm to poultry processing unit: A review - Pramila Umaraw; A. Prajapati; Akhilesh K. Verma; V. Pathak; V. P. Singh (Critical Reviews in Food Science and Nutrition, 2017)

Weed and Nitrogen Management Effects on Weed Infestation and Crop Productivity of Wheat–Mungbean Sequence in Conventional and Conservation Tillage Practices - C. P. Nath; T. K. Das; K. S. Rana; R. Bhattacharyya; H. Pathak; S. Paul; M. C. Meena; S. B. Singh (Agricultural Research, 2017)

Crop Diversification Options Involving Pulses and Sugarcane for Improving Crop Productivity, Nutritional Security and Sustainability in India - S. K. Shukla; K. K. Singh; A. D. Pathak; V. P. Jaiswal; S. Solomon (Sugar Tech, 2017)

The Vitamin E Analog Gamma-Tocotrienol (GT3) Suppresses Radiation-Induced Cytogenetic Damage - Rupak Pathak; Abdel Bachri; Sanchita P. Ghosh; Igor Koturbash; Marjan Boerma; Regina K. Binz; Jeffrey R. Sawyer; Martin Hauer-Jensen (Pharmaceutical Research, 2016)

Saline soil microbiome: A rich source of halotolerant PGPR - Shubhangi S. Hingole; Anupama P. Pathak (Journal of Crop Science and Biotechnology, 2016)

The Stress of Suicide: Temporal and Spatial Expression of Putative Heat Shock Protein 70 Protect the Cells from Heat Injury in Wheat (Triticum aestivum) - Ranjeet R. Kumar; Suneha Goswami; Richa Gupta; Pooja Verma; Khushboo Singh; Jyoti P. Singh; Mahesh Kumar; Sushil K. Sharma; Himanshu Pathak; Raj D. Rai (Journal of Plant Growth Regulation, 2016)

Anomalous Variation in GPS TEC, Land and Ocean Parameters Prior to 3 Earthquakes - Kunvar Yadav; Sheetal P. Karia; Kamlesh N. Pathak (Acta Geophysica, 2016)

Molecular Characterization of Commercial Varieties of Phyllanthus emblica Using RAPD and Nuclear rDNA SNPs - S. K. Singh; P. R. Meghwal; Rakesh Pathak (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Calcium triggers protein kinases-induced signal transduction for augmenting the thermotolerance of developing wheat (Triticum aestivum) grain under the heat stress - Suneha Goswami; Ranjeet R. Kumar; Sushil K. Sharma; Yugal K. Kala; Khushboo Singh; Richa Gupta; Gaurav Dhavan; Gyanendra K. Rai; Gyanendra P. Singh; Himanshu Pathak; Raj D. Rai (Journal of Plant Biochemistry and Biotechnology, 2015)

Vasculature-specific MRI reveals differential anti-angiogenic effects of a biomimetic peptide in an orthotopic breast cancer model - Eugene Kim; Esak Lee; Charlesa Plummer; Stacy Gil; Aleksander S. Popel; Arvind P. Pathak (Angiogenesis, 2015)

Homology Modeling and Comparative Profiling of Superoxide Dismutase Among Extremophiles: Exiguobacterium as a Model Organism - Rajiv Pathak; Pankaj Narang; Muktesh Chandra; Raj Kumar; P. K. Sharma; Hemant K. Gautam (Indian Journal of Microbiology, 2014)

Molecular Markers Assisted Identification of Intraspecific Hybrids in Ziziphus mauritiana - Sunil Kumar Singh; P. R. Meghwal; Rakesh Pathak; Ragini Gautam (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Assessment of Genetic Diversity Among Indian Jujube Varieties Based on Nuclear Ribosomal DNA and RAPD Polymorphism - S. K. Singh; P. R. Meghwal; Rakesh Pathak; R. K. Bhatt; Ragini Gautam (Agricultural Research, 2014)

Ascorbic acid at pre-anthesis modulate the thermotolerance level of wheat (Triticum aestivum) pollen under heat stress - Ranjeet R. Kumar; Suneha Goswami; Kritika A. Gadpayle; Khushboo Singh; Sushil K. Sharma; G. P. Singh; Himanshu Pathak; Raj D. Rai (Journal of Plant Biochemistry and Biotechnology, 2014)

Multiscale and multi-modality visualization of angiogenesis in a human breast cancer model - Jana Cebulla; Eugene Kim; Kevin Rhie; Jiangyang Zhang; Arvind P. Pathak (Angiogenesis, 2014)

Sugar Beet: A Historical Perspective in Indian Context - A. D. Pathak; Raman Kapur; S. Solomon; Rajesh Kumar; Sangeeta Srivastava; P. R. Singh (Sugar Tech, 2014)

Characterization of smallholder pig production system: productive and reproductive performances of local and crossbred pigs in Sikkim Himalayan region - B. G. Nath; P. K. Pathak; S. V. Ngachan; A. K. Tripathi; A. K. Mohanty (Tropical Animal Health and Production, 2013)

Thermally Triggered Mucoadhesive In Situ Gel of Loratadine: β-Cyclodextrin Complex for Nasal Delivery - Reena M. P. Singh; Anil Kumar; Kamla Pathak (AAPS PharmSciTech, 2013)

Multiscale Imaging and Computational Modeling of Blood Flow in the Tumor Vasculature - Eugene Kim; Spyros Stamatelos; Jana Cebulla; Zaver M. Bhujwalla; Aleksander S. Popel; Arvind P. Pathak (Annals of Biomedical Engineering, 2012)

Orchid Diversity: Conservation and Utilization - S. P. Vij; Promila Pathak (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2012)

Evaluation of bactericidal efficacy of silver ions on Escherichia coli for drinking water disinfection - Satya P. Pathak; K. Gopal (Environmental Science and Pollution Research, 2012)

In vivo laser speckle imaging reveals microvascular remodeling and hemodynamic changes during wound healing angiogenesis - Abhishek Rege; Nitish V. Thakor; Kevin Rhie; Arvind P. Pathak (Angiogenesis, 2012)

Studies on urban drinking water quality in a tropical zone - Mohana Krishna Reddy Mudiam; S. P. Pathak; K. Gopal; R. C. Murthy (Environmental Monitoring and Assessment, 2012)

GPS based TEC measurements for a period August 2008– December 2009 near the northern crest of Indian equatorial ionospheric anomaly region - S P KARIA; K N PATHAK (Journal of Earth System Science, 2011)

Bacterial Diversity of Lonar Soda Lake of India - Kshipra B. Deshmukh; Anupama P. Pathak; Mohan S. Karuppayil (Indian Journal of Microbiology, 2011)

Genomic mapping and testing for quantitative trait loci in tea (Camellia sinensis (L.) O. Kuntze) - S. M. Kamunya; F. N. Wachira; R. S. Pathak; R. Korir; V. Sharma; R. Kumar; P. Bhardwaj; R. Chalo; P. S. Ahuja; R. K. Sharma (Tree Genetics & Genomes, 2010)

Characterization of 2T engine oil degrading indigenous bacteria, isolated from high altitude (Mussoorie), India - Pankaj Kumar Jain; Vijai K. Gupta; Hardik Pathak; Madan Lowry; D. P. Jaroli (World Journal of Microbiology and Biotechnology, 2010)

Trade-off between productivity enhancement and global warming potential of rice and wheat in India - A. Bhatia; H. Pathak; P. K. Aggarwal; N. Jain (Nutrient Cycling in Agroecosystems, 2010)

Diagnosis of gastrointestinal tuberculosis: Using cytomorphological, microbiological, immunological and molecular techniques — A study from Central India - Pradyumna Kumar Mishra; A. Bhargava; R. P. Punde; N. Pathak; P. Desikan; A. Jain; S. Varshney; K. K. Maudar (Indian Journal of Clinical Biochemistry, 2010)

Role of nodD gene product and flavonoid interactions in induction of nodulation genes in Mesorhizobium ciceri - D. V. Kamboj; Ranjana Bhatia; D. V. Pathak; P. K. Sharma (Physiology and Molecular Biology of Plants, 2010)

Segment-2 sequence analysis and cross-neutralization studies on some Indian bluetongue viruses suggest isolates are VP2-variants of serotype 23 - Prabhakar A. Tembhurne; Bimalendu Mondal; Kunj B. Pathak; Sanchay K. Biswas; Aniket Sanyal; Mahendra P. Yadav; Santanu K. Bandyopadhyay; Raj K. Singh (Archives of Virology, 2010)

Eco-restoration of a high-sulphur coal mine overburden dumping site in northeast India: A case study - J. Dowarah; H. P. Deka Boruah; J. Gogoi; N. Pathak; N. Saikia; A. K. Handique (Journal of Earth System Science, 2009)

Novel blue light‐sensitive proteins from a metagenomic approach - G. P. Pathak; A. Ehrenreich; A. Losi; W. R. Streit; W. Gärtner (Environmental Microbiology, 2009)
Summary A microarray‐based approach was used to screen a soil metagenome for the presence of blue light (BL) photoreceptor‐encoding genes. The microarray carried 149 different 54‐mer oligonucleotides, derived from consensus sequences of light, oxygen and voltage (LOV) domain BL photoreceptor genes. Calibration of the microarrays allowed the detection of minimally 50 ng of genomic DNA against a background of 2–5 μg of genomic DNA. Identification of a positive cosmid clone was still possible for an amount of 0.25 ng against a background of 10 μg of labelled DNA clones. The array could readily identify targets carrying 4% sequence mismatch. Using the LOV microarray, up to 1200 library clones in concentrations of c . 20 ng each with a c . 40 kb insert size could be screened in a single batch. After calibration and reliability controls, the microarray was probed with cosmid‐cloned DNA from the thermophilic fraction of a soil sample. From this approach, a novel gene was isolated that encodes a protein consisting of several Per‐Arnt‐Sim domains, a LOV domain associated to a histidine kinase and a response regulator domain. The novel gene showed highest similarity to a known sequence from Kineococcus radiotolerans SRS30216 (58% identity for the LOV domain only) and to a gene from Methylibium petroleiphilum PM1 (57% identity). The gene, designated as ht‐met1 (Hamburg Thermophile Metagenome 1), was isolated and fully sequenced (3615 bp). ht‐met1 is followed by a second open reading frame encoding a Fe‐chelatase, an arrangement quite frequent for BL photoreceptors. The LOV domain region of ht‐met1 was subcloned and expressed yielding a fully functional, flavin‐containing LOV domain. Irradiation generated the typical LOV photochemistry, with the transient formation of a flavin‐protein photoadduct. The dark recovery lifetime was found as τ REC = 120 s (20°C) and is among the fastest ones determined so far for bacterial LOV domains.

Reproductive performance of crossbred dairy cows reared under traditional low input production system in the eastern Himalayas - A. Kumaresan; P. P. Prabhakaran; K. M. Bujarbaruah; K. A. Pathak; Bijoy Chhetri; S. K. Ahmed (Tropical Animal Health and Production, 2009)

Enhancement in alpha-tocopherol succinate-induced apoptosis by all-trans-retinoic acid in primary leukemic cells: role of antioxidant defense, Bax and c-myc - K. L. Khanduja; S. Kumar; N. Varma; S. C. Varma; P. K. Avti; C. M. Pathak (Molecular and Cellular Biochemistry, 2008)

Circulating and imaging markers for angiogenesis - Arvind P. Pathak; Warren E. Hochfeld; Simon L. Goodman; Michael S. Pepper (Angiogenesis, 2008)

Reproductive pathways of seed development in apomictic guinea grass (Panicum maximum Jacq.) reveal uncoupling of apomixis components - P. Kaushal; D. R. Malaviya; A. K. Roy; Shalini Pathak; A. Agrawal; Ambica Khare; S. A. Siddiqui (Euphytica, 2008)

Essential Metal Status, Prooxidant/Antioxidant Effects of MiADMSA in Male Rats: Age-related Effects - S. J. S. Flora; Ashish Mehta; Pratibha Gautam; P. C. Jatav; Uma Pathak (Biological Trace Element Research, 2007)

Modelling dust distributions in the atmospheric boundary layer on Mars - Peter A. Taylor; P-Y. Li; Diane V. Michelangeli; Jagruti Pathak; Wensong Weng (Boundary-Layer Meteorology, 2007)

Bacterial Contamination and Antibiotic Resistance in Fecal Coliforms from Glacial Water Runoff - S. P. Pathak; K. Gopal (Bulletin of Environmental Contamination and Toxicology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

RETRACTED ARTICLE: Engineered Polyallylamine Nanoparticles for Efficient In Vitro Transfection - Atul Pathak; Anita Aggarwal; Raj K. Kurupati; Soma Patnaik; Archana Swami; Yogendra Singh; Pradeep Kumar; Suresh P. Vyas; Kailash C. Gupta (Pharmaceutical Research, 2007)

Isolation and characterization of mutants of Pseudomonas maltophila PM-4 altered in chitinolytic activity and antagonistic activity against root rot pathogens of clusterbean (Cyamopsis tetragonoloba) - E. Yadav; D. V. Pathak; S. K. Sharma; M. Kumar; P. K. Sharma (Indian Journal of Microbiology, 2007)

Dynamics of Organic Carbon and Microbial Biomass in Alluvial Soil With Tillage and Amendments in Rice-wheat Systems - B. Banerjee; P. K. Aggarwal; H. Pathak; A. K. Singh; A. Chaudhary (Environmental Monitoring and Assessment, 2006)

Efficiency of Modified H2S Test for Detection of Faecal Contamination in Water - S. P. Pathak; K. Gopal (Environmental Monitoring and Assessment, 2005)

Toxicity of the Azo Dye Methyl Red to the Organisms in Microcosms, with Special Reference to the Guppy ( Poecilia reticulata Peters) - S. Sharma; S. Sharma; S. Pathak; K. P. Sharma (Bulletin of Environmental Contamination and Toxicology, 2003)

Effects of dicyandiamide, farmyard manure and irrigation on crop yields and ammonia volatilization from an alluvial soil under a rice ( Oryza sativa L.)-wheat ( Triticum aestivum L.) cropping system - Banerjee B.; Pathak H.; Aggarwal P. (Biology and Fertility of Soils, 2002)

The role of potassium in sustaining yields in a long-term rice-wheat experiment in the Indo-Gangetic Plains of Nepal - Regmi A.; Ladha J.; Pasuquin E.; Pathak H.; Hobbs P.; Shrestha L.; Gharti D.; Duveiller E. (Biology and Fertility of Soils, 2002)

Effect of Testosterone Suppression on the Pharmacokinetics of a Potent GnRH Receptor Antagonist - Eugenia A. Iatsimirskaia; Margaret L. Gregory; Kenna L. Anderes; Rosemary Castillo; K. Eric Milgram; David R. Luthin; Ved P. Pathak; Lance C. Christie; Haresh Vazir; Mark B. Anderson; John M. May (Pharmaceutical Research, 2002)

Long-term changes in yield and soil fertility in a twenty-year rice-wheat experiment in Nepal - Gami S.; Ladha J.; Pathak H.; Shah M.; Pasuquin E.; Pandey S.; Hobbs P.; Joshy D.; Mishra R. (Biology and Fertility of Soils, 2001)

Withania somnifera (Ashwagandha): Regeneration through Meristem Culture - Nilesh P. Teli; Nilima M. Patil; Hema M. Pathak; Sanjeevani R. Bhalsing; Vijay L. Maheshwari (Journal of Plant Biochemistry and Biotechnology, 1999)

Thyroid functions in lithium-treated psychiatric patients - S. D. Deodhar; B. Singh; C. M. Pathak; P. Sharan; P. Kulhara (Biological Trace Element Research, 1999)

HCH and DDT in Surface Extractable Skin Lipid as a Measure of Human Exposure in India - V. K. Dua; C. S. Pant; V. P. Sharma; G. K. Pathak (Bulletin of Environmental Contamination and Toxicology, 1998)

The Imperata grasslands of tropical Asia: area, distribution, and typology - D. P. Garrity; M. Soekardi; M. van Noordwijk; R. de la Cruz; P. S. Pathak; H. P. M. Gunasena; N. van So; G. Huijun; N. M. Majid (Agroforestry Systems, 1996)

Productivity of annual cropping and agroforestry systems on a shallow Alfisol in semi-arid India - M. R. Rao; C. K. Ong; P. Pathak; M. M. Sharma (Agroforestry Systems, 1991)